Оптимизация тепловых условий выращивания монокристаллов кремния методом Чохральского - Червоный, И. Ф.; Голев, Е. А. (НТУ "ХПИ", 2014)
Рассмотрены приемы оптимизации теплового узла для выращивания монокристаллов кремния методом Чохральского. Для создания заданных тепловых условий выращивания монокристаллов в конструкцию теплового узла вводятся дополнительные теплоизолирующие экраны и специальный верхний конусный экран. Совместное действие системы дополнительных экранов и расположение теплового узла позволило снизить непроизводительные потери тепла, в результате чего потребляемая нагревателем мощность снизилась на 33 %.

We propose an optimized thermal unit installation expressed schivani-ya-silicon single crystals by the Czochralski method with the introduction of additional thermal insulation screens and change the location of the main elements of the thermal unit in the cell cultivation. Upgraded heating unit contained three additional insulating screen made of a composite material based on carbon-coated pirografitovym: double screen cylinder forms the lower horizontal screen and the top screen of the conical shape. The combined action of additional screens and the location of the thermal unit, in the lowest possible position it possible to reduce wasteful heat loss, resulting in consumption of the heater power has decreased by 33 %. Impact of additional heat-insulating screen of conical shape has led to optimization of the temperature distribution on the surface of the silicon melt near the solidification front as well as the walls of the crucible and in the grown single crystal. It is possible to increase the speed of the single crystal growing by 44 % and the productivity of the process of growing by 34 %.
Optimization of thermal terms of growing of single-crystals of silicon by method of Czochralski
Keywords: полупроводниковые приборы; тепловой узел; теплоизолирующие экраны; конусный экран; потери тепла; мощность; тигель; градиент температуры; warm node; screen; heat capacity; crucible; melt gradient